Multi-channel real-time condition monitoring system based on wideband vibration analysis of motor shafts using SAW RFID tags coupled with sensors - Caldero Bardaji, Pau; Zoeke, Dominik (Sensors, 2019)
While there is a wide range of approaches to monitor industrial machinery through their static components, rotating components are usually harder to monitor, since sensors are difficult to be mounted on them and continuously read during operation. However, the characteristics of rotating components may provide useful information about the machine condition to be included in monitoring algorithms, specially for long-term data analysis. In this work, wireless vibration monitoring of rotating machine parts is investigated using surface acoustic wave (SAW) radio frequency identification (RFID) tags coupled with sensors. The proposed augmented transponder solution, combined with low-latency interrogation and signal processing, enables real-time identification and wideband vibration sensing. On top of that, a multi-channel interrogation approach is used to compensate motion effects. This approach enhances the signal-to-noise ratio of low-power high-frequency components present on the vibration signatures and enables discriminant information extraction from rotating machine parts. Final feasibility is evaluated with induction motors and vibration measurements on rotating shafts are verified. In addition, a condition classification algorithm is implemented in an experimental setup based on different motor states. The results of this work open the possibility to feed predictive maintenance algorithms using new features extracted in real-time from wideband vibration measurements on rotating components.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Augmented RFID; Condition monitoring; IIOT; SAW

SAW RFID Tag Spatial Division Multiple Access Based on 3D Reflector Response Localization Using a Wideband Holographic Approach - Caldero Bardaji, Pau; Gareis, Matthias; Vossiek, Martin (IEEE Journal of Microwaves, 2022)
Surface acoustic wave (SAW) radio-frequency identification (RFID) has high potential for industrial applications, where automated identification and localization of assets represent the backbone of process controlling and logistics. However, in situations where multiple tags are simultaneously interrogated, the response patterns corresponding to the hard-coded reflectors are prone to overlap, preventing their association with the corresponding tags and, hence, the correct tag decoding. Identification and localization of multiple SAW RFID tags are addressed in this work under this challenging effect, known as collision, with a multi-antenna mobile robot-based synthetic aperture approach. Using the estimation of the spatial probability density functions of the SAW tag reflectors over a given interrogation aperture, the received impulse responses can be resolved in three dimensions and clustered with respect to their estimated locations. The performance of the proposed approach to associate and localize the signals from multiple tags was evaluated theoretically and experimentally.<br
Keywords: 3D localization; anti-collision; RFID; SAW; SDMA

System concept for association and positioning of vehicles using SAW RFID tags - Caldero Bardaji, Pau; Zoeke, Dominik (EuRAD 2019 - 2019 16th European Radar Conference, 2019)
In this work we propose a system concept for simultaneous wireless identication and positioning of vehicles using SAW (surface acoustic wave) RFID (radio frequency identication) tags. Multichannel interrogation allows for additional extraction of vehicle orientation as well as resolution of ambiguities. The system is optimized for low-latency parallel interrogation with a measurement rate of 10 kHz to enable an accurate, real-time and unambiguous positioning with high statistical robustness, even for high-speed vehicles. Feasibility is demonstrated based on real experiments with tags mounted on an electronically controlled moving platform, showing its potential for localization and orientation measurements.
CRIS-Team Scopus Importer:2019-12-20
Keywords: Localization; Mobility; RFID; SAW